2011
DOI: 10.1159/000328776
|View full text |Cite
|
Sign up to set email alerts
|

Osthol, a Coumarin Isolated from Common Cnidium Fruit, Enhances the Differentiation and Maturation of Osteoblasts in vitro

Abstract: The effect of osthol on osteoblasts was investigated in primary osteoblastic cells isolated from newborn Wistar rats. Osthol was supplemented into cultured medium at 10–7, 10–6, 10–5 and 10–4 mol/l, respectively. No stimulating effect was found on cell proliferation, but 10–5 mol/l osthol caused a significant increase in alkaline phosphatase (ALP) activity. Osteogenic differentiation markers were examined over a period of time at this concentration, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 59 publications
1
50
0
Order By: Relevance
“…Specifically, the p38MAPK signaling pathway has a crucial role in the inflammatory response, regulating the cell cycle, cell differentiation and apoptosis [20,21]. Previous studies have shown that the p38MAPK signaling pathway has a close relationship with osteogenic differentiation of BMMSCs [2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the p38MAPK signaling pathway has a crucial role in the inflammatory response, regulating the cell cycle, cell differentiation and apoptosis [20,21]. Previous studies have shown that the p38MAPK signaling pathway has a close relationship with osteogenic differentiation of BMMSCs [2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…The p38MAPK signaling pathway plays a crucial role in the inflammatory reaction, regulation of the cell cycle, and cellular differentiation. Studies have demonstrated that the p38MAPK signaling pathway is related to osteogenic differentiation of BMMSCs [2][3][4][5][6]. Osterix is a recently discovered transcription factor related to bone formation as well as osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Osthole exhibits estrogen-like effects, and in ovariectomized rats, it can prevent osteoporosis and reduce bone loss [42]. Although the cellular effects of osthole on osteoblast proliferation and differentiation have been documented [43,44], the value of osthole as an adjuvant for cell sheet formation remains to be determined. We hypothesized that osthole administration would facilitate cell sheet formation, increase cell matrix production, and positively influence the cellular behavior of the sheet-grafted cells in terms of differentiation and maturation, and hence enhance tissue regeneration and functional integration following in vivo transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Ost has various pharmacological and biological applications, and current research is focused on its antitumor activity. Several previous studies have reported that Ost is effective in inducing cell apoptosis, arresting cell cycle, and inhibiting cell proliferation.…”
Section: Introductionmentioning
confidence: 99%